Optimal PMU Placement for Transmission Power Systems Considering Full Network Observability (Global Journals of Research in Engineering, 2023)
Installing a phasor measurement unit PMU at each bus in the power system network is very costly Thus selecting the optimal PMU placement is essential to avoid the high cost of the PMU and its corresponding communication facilities Most proposed efforts for the optimal PMU placement OPP considered only test systems without using any real systems which are more complicated On the other hand most researchers deal with the problem of PMU optimal placement as an optimization problem Hence solving the optimization problem may face difficulties such as the complicated analysis and the significant computational burden for the bulk large-scale networks This paper proposed a method to identify the optimal PMU placement achieving full observability over the entire network while avoiding optimization difficulties The proposed method is based on the Binary Particle Swarm Optimization BPSO technique and topological rules The Omani power grid is utilized as a large-scale network to apply the proposed method The OPP technique is carried out using DIgSILENT PowerFactory Programming language DPL and the results are validated on IEEE test systems 14 118 buses and NE 39 bus The results show that the proposed approach can achieve full observability of Oman s power system by installing PMUs in less than 24 of the system buses
Keywords: smart grid; PMUs; observability; optimal PMU placement; wide area monitoring; particle swarm optimization; topological rules